(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In the modern educational landscape, fostering creative competence has become essential for preparing students to address complex, real-world problems. This paper explores methods for developing creative competence in biochemistry lessons for future specialists, addressing both theoretical foundations and practical applications. This research is rooted in the premise that creativity in scientific fields, such as biochemistry, enhances problem-solving skills, fosters innovation, and equips students with critical thinking abilities necessary in their professional lives.